Balancing Tradition and Innovation: Energy-Efficient Hospitality Architecture in Bali's Growing Tourism Landscape - Putra, I Wayan Yogik Adnyana; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin; Putra, I Dewa Gede Agung Diasana (Universitas Ibn Khaldun Bogor, 2025)
Balinese hospitality architecture faces the challenge of integrating traditional Balinese design principles with modern energy-efficient technology while maintaining cultural authenticity. The study explores combining Balinese architectural heritage and contemporary innovations to achieve sustainability in the hospitality industry. Through a study of Tri Hita Karana-based spatial planning, passive cooling techniques, and the adoption of renewable energy, this study investigates how traditional elements such as bales, hogs, and open yards can be adapted to meet contemporary energy efficiency standards. Case studies of eco-friendly resorts, green hotels, and heritage-inspired developments illustrate how sustainable materials, climate-responsive clever design, and local energy solutions contribute to reducing the carbon footprint while maintaining the island's architectural identity. The findings highlight that blending vernacular wisdom with modern engineering solutions fosters resilience to climate change and improves the visitor experience. The study proposes a contextual model for sustainable hospitality architecture, offering practical guidelines for architects, developers, and policymakers that aim to align cultural preservation and environmental sustainability in the urbanization landscape.